Agricultural Marketing in Hailakandi District of Assam - Singha, Manindra (International Journal For Research In Business, Management And Accounting, 2018)
Agricultural marketing is one of the vital marketing system in Hailakandi District of Assam. Due to geographical location the district is very much fruitful for production of agricultural product but earlier the farmers were face to many problems but with the development of transportation system with compare to early period the farmers are now getting right price of their product. The district is one of the backwards district among other district of Assam from the survey report it is observed that the agricultural population account for 78 percent of the total population. Hence the agriculture remain economically important. The District is only 2 percent of total population is engaged industrial sector and expansion rate of Industries like small scale and large scale are very low in percentage.The existing practice of agricultural marketing in the Hailakandi District is a combination of informal and formal arrangements. As per the survey report the farmers of Hailakandi District of Assam are poor, illiterate and ignorant and due to these reasons, the trace of green revolution comes to this district a bit later. One more another important feature is that in Hailakandi District most of the farmers are belongs to marginal farmers so commercialization of agriculture s very struggle in the District.